Pengaruh Efisiensi, Persepsi Resiko dan Tingkat Kemudahan terhadap Keputusan Pembelian - Dewi yuliana; Heri Wijayanto; Edi Santoso (Universitas Muhammadiyah Ponorogo, 2020)
The study aims to determine the effects of efficiency, risk perception and ease in purchasing decisions ( a shopee consumer study in Ponorogo). The population in this study was that of online Shopee shop in Ponorogo, with a sample of 97 people. The method of sampling taken on this research uses the probability sampling with an technique simple random sampling. The data analysis used in this study is analysis of validity tests, reliability, multiple linear regression, classic assumption tests, t test, F test, and determinative coefficient R2. This shows that: 1) Variable X1 efficiency, positive for variable Y Shopee online shop purchase decisions in Ponorogo, 2). Variable X2 positive decision perceptions of Shopee purchasing decisions in Ponorogo, 3). Variable X3 a positive level of participation on the purchase decision of Shopee online stores in Ponorogo, 4). The independent variable consisted of efficiency, risk perception, and simultaneous success rates related to the decision to purchase Shopee's online store in Ponorogo.Keywords: efficiency, risk perception, ease levels, purchase decisions